2011
DOI: 10.1523/jneurosci.2387-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Zipcode Binding Protein 1 Regulates the Development of Dendritic Arbors in Hippocampal Neurons

Abstract: The pattern of dendritic branching, together with the density of synapses and receptor composition, defines the electrical properties of a neuron. The development of the dendritic arbor and its additional stabilization are highly orchestrated at the molecular level and are guided by intrinsic mechanisms and extracellular information. Although protein translation is known to contribute to these processes, the role of its local component has not been fully explored. For local translation, mRNAs are transported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 67 publications
4
89
1
Order By: Relevance
“…Cell Cultures, Transfection, and Drug Treatment-HEK293 cell culture, their transfection, and Western blot analysis were performed as described recently (30). The animals used to obtain neurons for tissue cultures were sacrificed according to a protocol approved by the First Ethical Committee, Warsaw, Poland.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell Cultures, Transfection, and Drug Treatment-HEK293 cell culture, their transfection, and Western blot analysis were performed as described recently (30). The animals used to obtain neurons for tissue cultures were sacrificed according to a protocol approved by the First Ethical Committee, Warsaw, Poland.…”
Section: Methodsmentioning
confidence: 99%
“…The animals used to obtain neurons for tissue cultures were sacrificed according to a protocol approved by the First Ethical Committee, Warsaw, Poland. Primary rat hippocampal and cortical cultures were prepared from embryonic day 18 (E18) rat brains according to Banker and Goslin (31) with modifications and transfected with Lipofectamine2000 (Invitrogen) as recently described (8,30). For insulin-induced growth, immediately after transfection, the cells were transferred to a regular culture medium that contained a reduced concentration of B27 (0.2% instead of 2%; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BDNF signaling induces the phosphorylation of ZBP1 and local synthesis of b-actin in growth cones, contributing to growth cone turning (Sasaki et al, 2010). In a recent study, ZBP1 was shown to regulate dendritic branching (Perycz et al, 2011). Interestingly, knockdown of ZBP1 inhibited the growth of dendritic protrusions in response to BDNF stimulation (Eom et al, 2003), suggesting that under limiting amounts of ZBP1 and b-actin mRNA in dendrites, neurons are not able to induce robust actin growth following stimulation with BDNF.…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 99%